(untitled) (Rhythmos, 2011)
Atrial fibrillation (AF) is the commonest cardiac arrhythmia afflicting 1% of the total population in an age-dependent manner with 2.3% of individuals older than 40 years of age, or 5.9% of people older than 65. Approximately 70% of persons with AF are between 65 and 85 years of age. Patients with AF experience significantly higher mortality rates than patients without AF; adjusted relative mortality risk has been found approximately 20% higher in patients with AF in all age-sex strata during each of the 3 years studied (P < 0.05). One sixth of all strokes are attributable to AF and the percentage of strokes due to AF increases dramatically with age; of course the risk of stroke is significantly decreased with anticoagulation therapy by 60-70%, but this has its own inherent problems. Unfortunately, the use of antiarrhythmic drugs (AADs) employed thus far to maintain sinus rhythm is severely problematic with treatment being occasionally worse than the disease. Nevertheless, the goal is still to maintain sinus rhythm, since teleologically this is the optimal rhythm man is born and should live with, but the means to effect and sustain this, have inherent potentially prohibitive risks, as shown in the AFFIRM, RACE and other trials. However, even in the AFFIRM trial, which showed that AADs may be associated with increased mortality, overall maintenance of sinus rhythm (with or without AADs) was associated with improved survival compared with persistent AF. This observation supports the long-recognized mortality risk associated with AF, and hence the continued quest for development of new and safer antiarrhythmic agents and methods to maintain sinus rhythm. In this endeavor, newer pharmacological agents have recently emerged but not yet fulfilled this expectation. Among them, dronedarone, a modified molecule of amiodarone devoid of the iodine moiety, was heralded as the agent with the new hope... (excerpt)